ANALISIS PENDAPATAN USAHATANI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI CABAI MERAH DI DESA TRIMULYO KECAMATAN TEGINENENG KABUPATEN PESAWARAN - Rahmadanti, Intan Sayna; Zakaria, Wan Abbas; Marlina, Lina (Lampung University, 2021)
This research aims to analyze income farming and factors affecting production of red chili in Trimulyo Tegineneng Pesawaran Regency. This research uses a survey method. Location of this research is chosen purposively in Trimulyo. The respondents are 60 red chili farmers taken by using a simple random sampling method. The income farming is determined using revenue cost ratio, while factors of production are analyzed by using Cobb Douglass. The results of the study showed that the income per hectare over cash costs obtained by farmers was IDR34,416,181.43 with R/C of 2.18 and income per hectare over total costs amounted to IDR24,520,886.39 with R/C of 1.63. Factors affecting production of red chili are land, seeds, KNO3 fertilizer, and pesticide. The R/C value that is greater than one means that red chili farming in Trimulyo Village Tegineneng Subdistrict Pesawaran Regency is profitable and feasible to be cultivated. Key words: income, production, red chili